Peran Departemen Engineering dalam Meningkatkan Kualitas Pelayanan Tamu di Hotel Horison Emerald Timoho Yogyakarta - Tri Hermanto; Agus Solikhin; Titik Akiriningsih (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Horison Emerald Timoho Yogyakarta Hotel is a four-star hotel in the Special Region of Yogyakarta committed to providing high-quality service and ensuring guest comfort. In the hospitality industry, service quality is influenced not only by departments that interact directly with guests but also by the Engineering Department, which plays a vital role in maintaining the reliability of hotel facilities and ensuring smooth operational activities. This study aims to identify the role of the Engineering Department in the operations of Horison Emerald Timoho Yogyakarta Hotel and to examine its contribution to improving guest service quality. This research employed a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation. The results indicate that the Engineering Department plays a significant role in supporting hotel operations through preventive maintenance, corrective maintenance, utility inspections, and prompt handling of guests' technical complaints. These roles contribute to maintaining guest comfort, safety, and satisfaction during their stay, thereby enhancing service quality and strengthening the competitiveness of Horison Emerald Timoho Yogyakarta Hotel.